The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1111/cei.12861
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the immune response toMycobacterium tuberculosisduring malaria/M. tuberculosisco-infection

Abstract: A note on versions:The version presented here may differ from the published version or from the version of record. If you wish to cite this item you are advised to consult the publisher's version. Please see the repository url above for details on accessing the published version and note that access may require a subscription. This article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process which may lead to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 35 publications
(38 reference statements)
1
30
0
1
Order By: Relevance
“…Although the first published report of malaria TB co-infection was in 1945, (227) there are only few papers published to date, including a case of perinatal malaria and TB in an infant (228), and several epidemiological surveys with prevalence varying from 37% in hospitalized adult and pediatric TB patients in Angola, to 4.3% among adult pulmonary TB patients in Tanzania (229, 230). Co-infections have been studied in both animal models and humans (226, 231234), and biological interactions seem to exist between P. falciparum, M. tuberculosis , and a shared human host.…”
Section: Malariamentioning
confidence: 99%
“…Although the first published report of malaria TB co-infection was in 1945, (227) there are only few papers published to date, including a case of perinatal malaria and TB in an infant (228), and several epidemiological surveys with prevalence varying from 37% in hospitalized adult and pediatric TB patients in Angola, to 4.3% among adult pulmonary TB patients in Tanzania (229, 230). Co-infections have been studied in both animal models and humans (226, 231234), and biological interactions seem to exist between P. falciparum, M. tuberculosis , and a shared human host.…”
Section: Malariamentioning
confidence: 99%
“…To understand the biological interaction between these two pathogens in vivo , infected mice with Mtb and, eight weeks later, with a non‐lethal P. yoelii strain, showed that the co‐infected mice were less able to contain the growth of Mtb in the lung, spleen and liver, thus increasing mortality . These results those of studies that demonstrate activation of TB after malaria exposure – evidence that malaria parasites can suppress host cellular and humoral immune responses during Mycobacterium tuberculosis (Mtb) infection . Disease control strategies for populations for which both diseases are endemic should consider the influence of increased incidence of one infection on the other .…”
Section: Discussionmentioning
confidence: 93%
“…Chen et al [28] analyzed the effect of HBV/TB coinfection in a retrospective investigation and showed that TB/HBV patients who did not receive anti-HBV treatment were more susceptible to Grade 4 drug-induced liver injury, liver failure, and poor outcomes compared with TB-monoinfected patients. Similarly, Chukwuanukwu et al [29] found that coinfection with TB and malaria weakened immune responses to TB and was associated with an increase in anti-inflammatory cytokine IL-10. However, coinfection may have enhanced the inflammatory response through increased T-helper 2-associated cytokines.…”
Section: Discussionmentioning
confidence: 96%